(1)(a+a^-1)^2=25, (a-a^-1)^2+4=24, (a-a^-1)^2=21, a-a^-1=根号21或-根号21。
(2)a^x-1=√2, (a^x-1)^2=2, a^2x-2a^x+1=2, a^2x-2a^x-1=0, a^x-a^-x=2
(a^2x-a^-2x)/(a^x+a^-x)=(a^x+a^-x)(a^x-a^x)/(a^x+a^-x)=a^x-a^-x=2.
第一小题√21第二小题2
(1)(a-a^-1)^2=a^2+1/a^2-2=(a+a^-1)^2-4=25-4=21
所以a-a^-1=±√21
(2)a^x=√2+1 a^-x=1/(√2+1)=√2-1
a^2x=(√2+1)^2=3+2√2 a^-2x=1/(3+2√2) =3-2√2
(a^2x-a^-2x)/(a^x+a^-x)=4√2/(2√2)=2
解:(1)因为a+a^-1=5
所以(a+a^-1)^2=a^2+a^-2+2=25
所以a^2+a^-2=23
又(a-a^-1)^2=a^2+a^-2-2=23-2=21
所以a-a^-1=+ -√21
(2)(a^2x-a^-2x)/(a^x+a^-x)=【(a^4x-1)/a^2x】/【(a^2x+1)/a^x】=【(a^4x-1)/a^2x】/【a^x/(a^2x+1)】=(a^4x-1)/【a^x(a^2x+1)】=【(a^2x+1)(a^2x-1)】/【a^x(a^2x+1)】=(a^2x-1)/a^x=a^x-a^-x
因为a^x=√2+1
所以(a^2x-a^-2x)/(a^x+a^-x)=a^x-a^-x=√2+1-1/(√2+1)=√2+1-(√2-1)/【(√2+1)(√2+1)】=√2+1-(√2-1)/1=√2+1-√2+1=2